Enforcement of Cross-Border Commercial Settlement Agreements: Application and Prospects of the Singapore Convention on Mediation in China - Zewei Ren (Law and Economy, 2024)
With the advancement of globalization, the importance of international commercial dispute resolution mechanisms has become increasingly prominent. The Singapore Convention on Mediation, as an important legal document in the field of international commercial Mediation, provides a unified legal framework for the enforcement of cross-border commercial settlement agreements and enhances the international status of Mediation as a means of dispute resolution. The article provides an in-depth analysis of the impact of the Convention on China’s commercial mediation system and its application in China, and discusses the challenges of the Convention to China’s legal system, especially the deficiencies in procedural norms, qualification of mediators, and the enforceability of mediation agreements. The article also examines the practice of Chinese courts in enforcing settlement agreements under the Convention, and points out the challenges that China faces in adapting to the requirements of the Convention in terms of the adaptability of its legal system, the need for adjustments in judicial procedures, the upgrading of the professional qualifications of mediators, and the strengthening of international cooperation. Finally, the article puts forward a series of policy recommendations to promote the effective implementation of the Convention in China and looks ahead to China’s potential role in the global commercial dispute resolution arena. Through an in-depth study of the Convention, the article aims to provide theoretical support and practical guidance for the development and internationalization of China’s commercial mediation system.